The relationship between blood lactate levels and mortality in pediatric intensive care patients. Issue 3 (2013) - Yolbaş, İlyas; Şen, Velat; Boşnak, Mehmet; Kelekçi, Selvi; Yel, Servet; Güneş, Ali
No abstract available